The influence of shared leadership on team performance with team personality composition as a moderating variable in student business project at Ciputra University Surabaya - Michelle Koesoema; Fanny Septina (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study was conducted to determine the effect of shared leadership and team performance with team personality composition as the moderating effect  on Ciputra University Student business project. In order to collect data, this study distributed questionnaires to 146 International Business Management students class of 2017 by using the purposive sampling method. In this study, an analysis of the variables of shared leadership, team performance and team personality composition were analyzed as moderators for shared leadership on team performance. The results of the study found that the shared leadership variable had a significant effect on team performance. Meanwhile, the team personality composition did not moderate the relationship between shared leadership and team performance.